Induction and characterization of a replication competent cervid endogenous gammaretrovirus (CrERV) from mule deer cells - Fábryová, Helena; Hron, Tomáš; Kabíčková, Hana; Poss, Mary; Elleder, Daniel (Virology, 2015)
Endogenous retroviruses (ERVs) were acquired during evolution of their host organisms after infection and mendelian inheritance in the germline by their exogenous counterparts. The ERVs can spread in the host genome and in some cases they affect the host phenotype. The cervid endogenous gammaretrovirus (CrERV) is one of only a few well-defined examples of evolutionarily recent invasion of mammalian genome by retroviruses. Thousands of insertionally polymorphic CrERV integration sites have been detected in wild ranging mule deer (Odocoileus hemionus) host populations. Here, we describe for the first time induction of replication competent CrERV by cocultivation of deer and human cells. We characterize the physical properties and tropism of the induced virus. The genomic sequence of the induced virus is phylogenetically related to the evolutionarily young endogenous CrERVs described so far. We also describe the level of replication block of CrERV on deer cells and its capacity to establish superinfection interference.
Keywords: Retrovirus interference; kokultivační techniky; Gammaretrovirus; Animals; Endogenous Retroviruses; virion; Genome, Viral; biologická evoluce; Cell Line, Tumor; HEK293 Cells; Virion; genom virový; lidé; replikace viru; Epithelial Cells; Deer; HEK293 buňky; Xenotropism; Phylogeny; endogenní retroviry; Endogenous retrovirus; Coculture Techniques; zvířata; Virus Replication; Biological Evolution; fylogeneze; epitelové buňky; vysoká zvěř; nádorové buněčné linie; Humans